Transition to Practice Experiences of New Graduate Nurses From an Accelerated Bachelor of Science in Nursing Program: Implications for Academic and Clinical Partners. - Wiersma, Gretchen; Pintz, Christine; Fraser Wyche, Karen (Journal of Continuing Education in Nursing, 2020)
Background: This study explored the transition to practice experiences of new graduate nurses and the effects of their education on their readiness to practice. Method: This phenomenological study used two focus groups to gain an in-depth understanding of the lived experiences of these graduate nurses during their first year of practice, their perceptions of the effectiveness of their academic experience in preparing them for professional nursing practice, and clinical agency support. Results: Three themes emerged from the focus group analysis: Practice Readiness, Work-Related Environmental Influences, and Being a Nurse. Conclusion: This study provides insight into the key issues surrounding the transition process experienced by new nurses and suggests ways to educate and successfully transition them into professional practice. Information gained from this study provides a beginning evidence base for other educators in both the academic and clinical settings interested in supporting successful transition to practice for new graduate nurses. This study provides insight into the key issues surrounding the transition process experienced by new nurses and suggests ways to educate and successfully transition them into professional practice. Information gained from this study provides a beginning evidence base for other educators in both the academic and clinical settings interested in supporting successful transition to practice for new graduate nurses. [[J Contin Educ Nurs. 2020;51(9):433–440.]